RETRACTED: Machine learning approaches for water potability prediction: Addressing class imbalance with SMOTE - Stepanova Elina; Orlov Vasiliy; Kukartsev Vladislav; Pinchuk Ivan; Suprun Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001